Problem relating to Corporate Governance in Pakistan - Aziz, Muhammad; Gondal, Zahid Hafeez; Ali, Sajid (Advances in Social Sciences Research Journal, 2019)
Corporate governance refers to the system in which companies controlled. Good Corporate governance stand on the principle of transparency, accountability, responsibility and fairness. It is very crucial for Pakistani companies for attaining better position in the global market in that kind of situation. This study focuses on the problems that creating hurdles corporate governance in Pakistan. In Pakistan mostly companies didn’t show their full potential because of several reason mostly companies based in Pakistan are run on traditional ways and unable to meet with international standards, Due to worth of companies decreasing day by day. Mostly companies are family owned due to this they take low risk and didn’t go for latest technology and on the other hand there is lack of independent directors who gave their independent view about the financial health of the company. If they heir the expertise of Ned’s they gave only a fixed fee or only paying annual meeting attending fee due to this Ned’s or professional engage with own work and they stay away. Pakistani companies desire to get better position an international market. But unfortunately they are very far away for attaining their desire result because they faced many problems in corporate especially governance issues. There is also top heavy system of information pass through and they take long time due to this creating problem in decision taking. And few other problems like conflict of interest, low remuneration, qualified staff, misuse of powers and lots more.